REFORMASI PELAKSANAAN MODEL PEMBINAAN YANG EFEKTIF TERHADAP KINERJA PEGAWAI DI KANTOR KECAMATAN NANGGALO KOTA PADANG - Fajri Valentino; Syamsir Syamsir; Rahmadya Aydini; Nora Juni Amefa; Tricillia Agustina; Muhammad Raihan (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2022)
The demands for reform have had an impact on various areas of life, including the administration of the civil service. Reform in the personnel sector which is a consequence of changes in the political, economic and social fields. Employee development is all efforts to improve capabilities in carrying out general government and development tasks. Employee development is carried out for the growth and continuity of the quality of employees in an organization. The purpose of this study is to find out about employee development by the sub-district head in the Nanggalo sub-district office including obstacles, efforts, types of leadership, and evaluation. This research method is descriptive research. Descriptive research can be interpreted as research whose purpose is to describe accurately and systematically handle the characteristics, circumstances or frequency of relationships in certain individuals. Employee development is carried out by the leadership - the sub-district office directly, employee development is assisted and under the control of the sub-district secretary, for his own development, namely through training based on existing techniques.